Pengembangan Acetylated Cellulose Nanofibers dari Microcrystalline Cellulose: Studi Perubahan Gugus Fungsi dan Indeks Kristalinitas melalui Asetilasi dan Nanofibrilasi - Kusmono, Kusmono; Risda Azizah, Hasn (Journal of Mechanical Engineering, 2024)
Cellulose nanofiber (CNF) has promising potential as a reinforcement in polymer matrix nanocomposites. CNF is polar or hydrophilic due to having many hydroxyl groups. When CNF particles are combined with a non-polar polymer matrix, the CNF is difficult to distribute evenly and tends to agglomerate due to differences in polarity so that the strengthening effect of CNF is limited. To overcome this problem, it is necessary to chemically modify the CNF surface. Acetylation is one of the most widely used CNF surface modification methods to increase the compatibility between a non-polar polymer matrix and CNF. Through the acetylation process, some of the hydroxyl groups of CNF are replaced with acetyl groups which are hydrophobic. Furthermore, the CNF resulting from the acetylation process is known as acetylated CNF (acetylated cellulose nanofibers or ACNF). The acetylation process is carried out by first mixing microcrystalline cellulose (MCC) particles into 75 mL of acetic anhydride solution. Next, the mixture was stirred using a high-speed blender for 30 minutes for the MCC nanofibrillation process to occur. In this research, the influence of acetylation and nanofibrillation processes on the characteristics of ACNF was studied through studying chemical structure changes using ATR-FTIR and crystallinity index using XRD. The results of the ATR-FTIR analysis show that there are 3 new peaks in the ACNF spectrum, namely at 1720, 1369 and 1203 cm-1, which proves that there is a change in the structure of cellulose after being given acetylation treatment. The results of XRD show that surface treatment of acetylation and nanofibrillation with a high-speed blender increases the ACNF crystallinity index value by 82.53%. Overall, the resulting ACNF has great potential as a reinforcement for polymer matrix nanocomposites.